The relationship between heel pad compressibility index, age, body mass index and foot area contact in calcanea spur patients - Wibowo, Dwi Basuki; Suprihanto, Agus; Haryadi, Gunawan Dwi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
This study was performed to investigate the relationship between heel pad compressibility index (HPCI), age, body mass index (BMI) and (FAC) for calcanea/heel spur patients. Thirteen patients with a symptomatic heel spur (3 males and 10 females) participated in this study. The HPCI increased with age and HPCI of the elderly is greater than the adult. The HPCI increased with pain minimum compressive pressure (PMCP) indicated HPCI are all significantly greater in patients with plantar heel pain than in normal subjects. The BMI increased with FAC is caused by BMI and FAC of males is greater than females. The PMCP decreased with BMI indicated that patient with excessive body mass will make experience more pain. The result of pain measurement showed that there are 7 patients who indicated the abnormality (the PMCP value is lower than 2 kg/cm2). From this study, it can be concluded that the quantitatively pain level is worst when PMCP< 2.0 kg/cm2, it is severe when 3.0> PMCP â‰¥ 2.0 kg/cm2 and it is moderate when PMCPâ‰¥3.0 kg/cm2